Successful Late Treatment of Orbital Infantile Haemangiomas in Two Teenagers with Topical Transcutaneous Timolol Maleate 0.5% Alone - Hildebrand, Göran Darius; Sipkova, Zuzana (Klinische Monatsblätter für Augenheilkunde, 2022)
We previously described the first successful treatment of deep periocular and, subsequently, orbital infantile haemangiomas (IH) with topical transcutaneous timolol maleate 0.5% (TM 0.5%) alone as the first-line treatment in the acute proliferative phase in infancy. It is not known whether orbital IH with persistent proptosis in later years, untreated in infancy, would still respond to TM 0.5% treatment as well. To our best knowledge, we here present the first reports of the successful late treatment of persistent orbital IH with topical timolol maleate 0.5% applied to the skin overlying the orbital IH in two teenagers. Case 1 was an 11-year-old girl with proptosis measuring 4 mm before and 7 mm after Valsalva manoeuvre that diminished to 1 mm after topical treatment. Case 2 was a 10-year-old girl with 2 mm (before) and 4 mm proptosis (after Valsalva) that decreased to 0 mm proptosis with topical treatment. The time to resolution was 19 months (case 1) and 13 months (case 2). The treatment dose was 3 drops of TM 0.5% applied an average of 1.94 (case 1) and two times daily (case 2). In comparison to proptosis, resolution of periorbital swelling required less treatment time. There was no recurrence of either proptosis or periorbital swelling 1 year after stopping treatment in either case. The findings indicate that beta-blockers are effective not just in the proliferative but also in the late involutional phase in older children. No adverse clinical effects were noted throughout treatment in either case. The presence of increased proptosis with a Valsalva manoeuvre predicts a significant persistent vascular compartment in the orbital IH and may thus serve as a simple predictive clinical sign of likely treatment success. We recommend that a trial with this well-tolerated treatment form is considered in persistent cases of orbital IH, especially in the presence of enhanced proptosis with a Valsalva manoeuvre.
Keywords: topical beta-blocker; orbital infantile haemangioma; orbital capillary haemangioma; late treatment; transcutaneous topical timolol